The Development of Textbooks On Circumference And Area Of Flat Shapes Material For Grade IV Elementary School - Titik Handayani; Ismail Marzuki; Nanang Khoirul Umam (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
The development of this textbook aims to be able to assist students in self-study at home as well as teachers in understanding students, especially in the topic of ​​circumference and area of ​​ two-dimensional figure. This research is a textbook development research using 3 of the 4 steps of the 4D Development Model, namely Define (defining), Design (design), Development (development). The results of the media in the form of Textbooks of the topic Circumference and area of ​​ two-dimensional figure. The data obtained from this study were teacher interviews and validation of learning media. There are four kinds of validation sheets used, namely one for material validation, presentation validation, linguistic validation, and graphic validation. Based on the expert validator's assessment of the Circumference and area of ​​ two-dimensional figure Textbooks for Grade IV Elementary School, the results of the material validator's assessment showed an average value of 90% which was categorized as valid. The results of the language validator show an average value of 91.6% which is categorized as valid. The results of the presentation validator show an average of 85.4% so it is categorized as valid. The results of the graphical validator show an average value of 95.8% which can be categorized as valid. The assessments of the validators can be said as valid with a few revisions or additions to complete the textbook. Keywords : 4D Model, Textbook, Perimeter and Area, two-dimensional figure